‘Camp Syndrome?’ Exploring Frontier Masculinity in Alberta’s Oil Production Culture: Oil Worker and Sex Worker Perspectives - Landry, Kassandra M. (University of Alberta, 2017)
Research shows that the sex trade flourishes in oil rich regions and economies. However, the connection between these two industries has not been widely studied despite how studies often acknowledge that oil industry workers purchase sexual services. This thesis, therefore, explores how the oil production culture contributes to oil industry workers purchasing sexual services. This research project aims to explore answers to the following research questions: 1) How does the oil production culture contribute to oil industry workers purchasing sexual services; 2) What economic and social aspects of the oil production culture contribute to oil industry workers purchasing sexual services; and 3) What can we learn about the sex trade and the oil industry when using a feminist lens? In addition, this research project draws from literature on masculinity, Messerschmidt’s theoretical work on masculinity, and feminist theory. I used a qualitative exploratory methodology to answer the research questions. In total, I conducted 11 semi-structured interviews, including five oil industry workers and six indoor sex workers. My major findings suggest that there is a strong economic connection between the oil industry and sex trade, as well as that negative views of women, the objectification of women, and the normalization of purchasing sex, are all pervasive aspects of the oil production culture. However, the negative treatment of women within the oil industry seems to be context specific to the oil production culture insofar as I also found there are no significant differences in sex workers’ interactions with oil industry worker clients compared to non-oil industry worker clients. I conclude that the frontier masculinity found in the oil production culture is an expression of masculinity specific to the context of the oil industry. This thesis, then, offers contributions on three main topics: what it is like working in the oil industry; the lifestyle and culture of the oil industry; and the connection Alberta’s oil industry has to indoor sex work.